Students’ Voices on an English Material for Accounting Major At SMK Negeri 2 Kota Jambi - Suyadi Suyadi (Universitas Batanghari Jambi, 2020)
English for specific purposes which is aimed at developing a specific English material for the students of accounting major is important aspect due to as the specification of materials for teaching English at Vocational Senior High School 2 is needed by the students. This research is aimed at the students’ voices on the specific material needed by the students at accounting major would be become an end result of English teaching material. This research is aimed at finding specific English materials for accounting major at Vocational Senior High School 2 of Jambi City. Some structured-questions were distributed to arrange the students’ interests of the specific materials. This research was conducted in two classes of SMK Negeri 2 Kota Jambi using a qualitative research. A thematic analysis was implemented in relation to the specific English materials used in the classroom. The findings reveal that some materials are matched with accounting major but some others are not. The materials for accounting major are compiled in a handbook of English material for accounting students which are two chapters of materials; Introduction to Accounting and Conceptual Framework of Accounting.